Interior Design Principles for Well-Being in Supporting a Therapeutic Environment - Gracia Veronica; Rizky Nurfitri Chairany (Graduate School of Institut Seni Indonesia Yogyakarta, 2026)
Interior design plays an important role in shaping the quality of environments that support the psychological well-being of space users, particularly in the context of activity-based therapy spaces. This study aims to examine how the application of interior wellbeing principles through ergonomic approaches and sensory experience management can support psychosocial regulation in therapeutic practice. This approach positions space not merely as a container for activities but also as a medium that contributes to the therapeutic process. This study employs a qualitative approach through literature review and conceptual analysis of the relationships between ergonomics, spatial arrangement, and interior environmental quality, such as lighting and acoustics. The findings indicate that environments designed with consideration for bodily stability, environmental stimulation control, and clear spatial organization can create conditions that support self-reflection, concentration, and emotional balance among space users. The integration of comfortable lighting, controlled acoustic quality, and ergonomic furniture arrangement enables a balanced sensory experience, allowing users to interact with the space in a more stable and focused manner. The findings of this study indicate that the application of interior wellbeing principles contributes to supporting the psychosocial regulation process, characterized by emotional stability, enhanced focus, psychological comfort, and deeper engagement in therapeutic activities. As such, interior design holds potential as an integral component in activity-based therapeutic practice. This study affirms that the integration of ergonomics, sensory experience, and interior environmental quality can serve as an important conceptual framework in the development of human well-being-oriented therapy spaces. Prinsip-prinsip Desain Interior untuk Kesejahteraan dalam Mendukung Lingkungan Terapi Abstrak Desain interior memiliki peran penting dalam membentuk kualitas lingkungan yang mendukung kesejahteraan psikologis pengguna ruang, khususnya dalam konteks ruang terapi berbasis aktivitas. Penelitian ini bertujuan untuk mengkaji bagaimana penerapan prinsip interior wellbeing melalui pendekatan ergonomi dan pengelolaan pengalaman sensori dapat mendukung regulasi psikososial dalam praktik terapi. Pendekatan ini menempatkan ruang tidak hanya sebagai wadah aktivitas, tetapi juga sebagai medium yang berkontribusi terhadap proses terapeutik. Kajian ini menggunakan pendekatan kualitatif melalui studi literatur dan analisis konseptual terhadap hubungan antara ergonomi, penataan ruang, serta kualitas lingkungan interior seperti pencahayaan dan akustik. Hasil kajian menunjukkan bahwa lingkungan yang dirancang dengan mempertimbangkan stabilitas tubuh, pengendalian stimulasi lingkungan, serta organisasi ruang yang jelas dapat menciptakan kondisi yang mendukung refleksi diri, konsentrasi dan keseimbangan emosional pengguna ruang. Integrasi antara pencahayaan yang nyaman, kualitas akustik yang terkendali, serta penataan furniture yang ergonomis memungkinkan terciptanya pengalaman sensori yang seimbang sehingga pengguna dapat berinteraksi dengan ruang secara lebih stabil dan terfokus. Temuan penelitian ini menunjukkan bahwa penerapan prinsip interior wellbeing berkontribusi dalam mendukung proses regulasi psikososial yang ditandai oleh stabilitas emosi, peningkatan fokus, kenyamanan psikologis, serta keterlibatan yang lebih mendalam dalam aktivitas terapi. Dengan demikian, desain interior memiliki potensi sebagai bagian integral dalam praktik terapi berbasis aktivitas. Penelitian ini menegaskan bahwa integrasi antara ergonomi, pengalaman sensori dan kualitas lingkungan interior dapat menjadi kerangka konseptual penting dalam pengembangan ruang terapi yang berorientasi pada kesejahteraan manusia.